Tertiary Lymphoid Structure-B Cells Narrow Regulatory T Cells Impact in Lung Cancer Patients - Germain, Claire; Devi-Marulkar, Priyanka; Knockaert, Samantha; Biton, Jérôme; Kaplon, Hélène; Letaïef, Laïla; Goc, Jérémy; Seguin-Givelet, Agathe; Gossot, Dominique; Girard, Nicolas; Validire, Pierre; Lefèvre, Marine; et al. (Frontiers in Immunology, 2021)
The presence of tertiary lymphoid structures (TLS) in the tumor microenvironment is associated with better clinical outcome in many cancers. In non-small cell lung cancer (NSCLC), we have previously showed that a high density of B cells within TLS (TLS-B cells) is positively correlated with tumor antigen-specific antibody responses and increased intratumor CD4+ T cell clonality. Here, we investigated the relationship between the presence of TLS-B cells and CD4+ T cell profile in NSCLC patients. The expression of immune-related genes and proteins on B cells and CD4+ T cells was analyzed according to their relationship to TLS-B density in a prospective cohort of 56 NSCLC patients. We observed that tumor-infiltrating T cells showed marked differences according to TLS-B cell presence, with higher percentages of naïve, central-memory, and activated CD4+ T cells and lower percentages of both immune checkpoint (ICP)-expressing CD4+ T cells and regulatory T cells (Tregs) in the TLS-Bhigh tumors. A retrospective study of 538 untreated NSCLC patients showed that high TLS-B cell density was even able to counterbalance the deleterious impact of high Treg density on patient survival, and that TLS-Bhigh Treglow patients had the best clinical outcomes. Overall, the correlation between the density of TLS-Bhigh tumors with early differentiated, activated and non-regulatory CD4+ T cell cells suggest that B cells may play a central role in determining protective T cell responses in NSCLC patients.